Perancangan Turbin Archimedes Kapasitas 700 Watt untuk Aliran Sungai Dangkal - Zhilal Ihsan Ilahi; Reza Afriansyah; Angga Zuga Prasetiyo; Fathan Mukhlis; Choirul Anwar (ELASTICITY: Journal of Applied Engineering Science, 2025)
Archimedes turbines are a renewable energy technology that utilizes the kinetic energy of water flows to generate electricity. This technology is suitable for use in locations with low water drop heights, where traditional turbine technology is less efficient. This research aims to design and calculate the main parameters of Archimedes turbines with high efficiency. The methods used include the collection of initial data such as discharge and water flow velocity, calculation analysis using gear ratios, and design simulations to validate the strength of the structure. Design parameters include turbine diameter of 0.276 meters, length of 1 meter, and tilt of 30°. The simulation results show that the turbine is able to operate at a speed of 113.88 rpm and produce 741.5 watts of electrical power with an efficiency of 85%. The main conclusion of the study is that Archimedes turbines have great potential as a renewable energy solution for areas with high water fall. Further implementation in the field is needed to validate these results and evaluate environmental impacts.